Implementasi Dan Pelatihan Google Apps For Education (GAFE) Untuk Pesantren Muhammadiyah Kabupaten Tasikmalaya Pada Masa Pandemi Covid-19 - Randi Rizal; Ruuhwan Ruuhwan; Aso Sudiarjo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Changes in business processes, lifestyles and ways of working that are more effective and efficient are caused by the rapid development of technology in various fields of human life, especially education. The current service partner is the Muhammadiyah Islamic Boarding School in Tasikmalaya Regency which has problems in optimizing educational activities in the pesantren environment. The use of features in Google Apps For Education (GAFE) is not optimal in educational activities, both in the teaching process between teachers and students, subject assignments, or other educational administration activities, so it is necessary to use these features more optimally. In addition, it is a new thing for teachers and students in optimizing the use of Google Apps for Education (GAFE), which makes it difficult and requires assistance to be used. This service provides alternative solutions for partners, namely the implementation and training of Google Apps for Education (GAFE) technology for teachers and students in an effort to improve skills and culture of responsiveness to the maximum use of technological developments so that it has an impact on the ease and smoothness of the online learning process.